Non-Palladium-Catalyzed Oxidative Coupling Reactions Using Hypervalent Iodine Reagents - Shetgaonkar, Samata E.; Raju, Aleena; China, Hideyasu; Takenaga, Naoko; Dohi, Toshifumi; Singh, Fateh V. (Frontiers in Chemistry, 2022)
Transition metal-catalyzed direct oxidative coupling reactions via C–H bond activation have emerged as a straightforward strategy for the construction of complex molecules in organic synthesis. The direct transformation of C–H bond into carbon–carbon and carbon-heteroatom bonds renders the requirement of prefunctionalization of starting materials and therefore represents a more efficient alternative to the traditional cross-coupling reactions. The key to the unprecedented progress made in this area has been the identification of appropriate oxidant that facilitates oxidation as well as provides heteroatom ligands at the metal centre. In this context, hypervalent iodine compounds have evolved as mainstream reagents particularly due to their excellent oxidizing nature, high electrophilicity and versatile reactivity. They are environmentally benign reagents, stable, non-toxic and relatively cheaper than inorganic oxidants. For many years, palladium catalysis has dominated these oxidative coupling reactions, but eventually other transition metal catalysts such as gold, copper, platinum, iron, etc. were found promising alternate catalysts for facilitating such reactions. This review article critically summarizes the recent developments in non-palladium-catalyzed oxidative coupling reactions mediated by hypervalent iodine(III) reagents with great emphasis on understanding the mechanistic aspects in details.